2013
DOI: 10.1111/apa.12245
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiography allows more accurate placement of peripherally inserted central catheters in low birthweight infants

Abstract: This study demonstrated the value of echocardiography for identifying the positioning of catheter tips in LBW infants. Echocardiography, coupled with initial plain radiographs, should be the gold standard for assessing PICC tip positions in those infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 16 publications
1
37
0
3
Order By: Relevance
“…However, radiography has not been able to do this properly (16,17). Results of previous studies have indicated that ultrasound can minimize the potential side effects of improper catheter placement and reduce the need for radiography reassessment (18,19), which was confirmed in the present study.…”
Section: Discussionsupporting
confidence: 69%
“…However, radiography has not been able to do this properly (16,17). Results of previous studies have indicated that ultrasound can minimize the potential side effects of improper catheter placement and reduce the need for radiography reassessment (18,19), which was confirmed in the present study.…”
Section: Discussionsupporting
confidence: 69%
“…23 However, XRs are unreliable in determining exact CTP and several studies strongly suggest that RTUS instead should be considered the "gold standard" to confirm correct CTP in neonates. 4,5,8,12,13 The limitations and technical difficulties of US and RTUS scanning likely prevent US from supplanting XR as the standard of care for line verification at the current time. Even when done by trained radiologists and cardiologists, the ability to detect the CTP by US ranges from 90 to 100% compared with essentially 100% by XR.…”
Section: Discussionmentioning
confidence: 99%
“…7,18 Multiple authors advocate that RTUS done by neonatologists can minimize potential complications from line malposition and reduce XR assessments. 5,8,15,16,20 Jain et al described clinical benefit with targeted neonatal echocardiography by intensivists immediately after insertion for better determination of CTP. 6 Three studies, two of which originate from the same institution, describe bedside RTUS-guided insertions by neonatologists with varying degrees of success.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common, plain radiography is plagued with concerns about poor intra- and inter-observer reliability[ 2 ]. Other modalities, e.g ., echocardiography[ 3 ] and CT[ 4 ] might be more reliable but are not readily available in most units. Use of contrast, an injectable solution that can be used to improve radio-opacity of the longline by injecting into the longline in sufficient volume to fill the connecting device and catheter, can help with recognition of unusual patterns of contrast medium dispersal and lead to easier identification of catheter malposition when combined with radiographs[ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%